1997
DOI: 10.1007/bf02445052
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and lymph electrolyte and endocrine parameters in rats with genetically-determined arterial hypertension

Abstract: Hemolymphatic interactions of electrolytes and plasma contents of aldosterone and insulin are studied in rats with genetically-determined stress-induced arterial hypertension (NISAG) and in normotensive rats (Wistar). Correlation analysis shows that alterations in electrolyte metabolism in NISAG are strongly determined by endocrine influences. These alterations are regarded, on the one hand, as a mechanism responsible for generically-determined arterial hypertension, and, on the other hand, as a variant of "ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Diuretics act by diminishing sodium chloride reabsorption at different sites in the nephrons, thereby increasing urinary sodium chloride and water losses and consequently leading to decreased plasma levels of these electrolytes. Antonov et al [ 24 ] reported that plasma electrolyte contents increased significantly in hypertensive rats. Impaired function of Na, K-ATPase and the Na-H antiport, which is typical of arterial hypertension, may promote an increase in plasma electrolytes.…”
Section: Resultsmentioning
confidence: 99%
“…Diuretics act by diminishing sodium chloride reabsorption at different sites in the nephrons, thereby increasing urinary sodium chloride and water losses and consequently leading to decreased plasma levels of these electrolytes. Antonov et al [ 24 ] reported that plasma electrolyte contents increased significantly in hypertensive rats. Impaired function of Na, K-ATPase and the Na-H antiport, which is typical of arterial hypertension, may promote an increase in plasma electrolytes.…”
Section: Resultsmentioning
confidence: 99%
“…Many diuretics act by diminishing sodium chloride reabsorption at different sites in the nephrons, thereby increasing urinary sodium chloride and water losses, and consequently leading to decreased plasma levels of these electrolytes. Antonov et al [ 23 ] reported that plasma electrolyte contents increase significantly in hypertensive rats. Impaired function of Na, K-ATPase, Na-H antiport, which is typical of arterial hypertension, may promote an increase in plasma electrolytes.…”
Section: Resultsmentioning
confidence: 99%
“…Diuretics act by diminishing sodium chloride reabsorption at different sites in the nephrons, thereby increasing urinary sodium chloride and water losses, consequently leading to decreased plasma levels of these electrolytes. Antonov et al [ 25 ] reported that plasma electrolyte contents increased significantly in hypertensive rats. Impaired function of Na, K-ATPase and the Na-H antiport, which is typical of arterial hypertension, may promote an increase in plasma electrolytes.…”
Section: Discussionmentioning
confidence: 99%